COST ASSESSMENT FOR INTEGRATED LOGISTIC SUPPORT ACTIVITIES - Nenni, Maria Elena (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
An Integrated Logistic Support (ILS) service has the objective of improving a system’s efficiency and availability for the lifecycle. It is usually offered to the customer by the system’s constructor, who becomes the Contractor Logistic Support (CLS). The aim of this paper is to propose a specific cost model for supporting the CLS management during the budgeting and negotiation phases for ILS activities. Specific goals of the model are provisioning annual cost of ILS activities and a comprehensive examination of expected benefits, costs and savings under alternative ILS strategies. A simple example derived from an industrial application is also provided in order to illustrate the idea.